Navigatio libera. - Gröning, Johann, 1669-1706
1 online resource.
Keywords: The original Latin text of Johann Gröning’s Navigatio libera has never before been translated into any modern vernacular language. Gröning’s intention was to set out the position of neutral nations (in this case the Danes and Swedes), and their right to pursue trade during the wars of the great maritime powers (particularly the English and the Dutch). It specifically sought to engage with and refute the work of Hugo Grotius while taking cognisance of the critique of Gröning’s work by Samuel Pufendorf. The text serves as a bridge between 17th-century polemical discourse surrounding the ‘free sea’ versus ‘enclosed sea’ debate and later 18th-century legal literature on the rights of neutrals and the continuation of free trade in time of war.